Treatment of Wastewater Generated by Wood-Based Dry Industry and Municipal Wastewater for Microalgae Cultivation - Vehapi, Meyrem; Inan, Benan; Ozcimen, Didem (Mehmet Sinan Bilgili, 2020)
In order to develop a sustainable microalgal bioprocess, it is necessary to increase process efficiency, maximize production yield and reduce production expense such as cost of commercial growth medium. In this context, researchers are evaluating various wastewaters for microalgae growth. However; most of the wastewater types cannot be utilized without dilution due to their composition which can have some organic compounds that may affect microalgae growth in a negative way. The aim of this study was to investigate the effects of Iroko tree water and municipal wastewater on microalgae production. In this study, C. vulgaris and C. minutissima microalgae species were cultivated with these different growth mediums. Conditions of cultivation parameters such as light, temperature, mixing speed and pH were set to be the same for each strain. 30% (v/v) concentrations of Iroko tree water and municipal wastewater were added to the freshwater growth medium. Biomass growth was measured, and growth kinetics of different cultivation medium were evaluated. In addition, chlorophyll and carotene content of microalgae species grown in different wastewaters as cultivation media was compared. With this study, Iroko tree water has been found to be more favorable to the growth of Chlorella species than municipal wastewater. Among two species, C. minutissima microalgae reached high concentrations in all culture medium and showed higher growth than C. vulgaris.
Keywords: Microalgae; C. vulgaris; C. minutissima; tree water; municipal wastewater; Engineering; Environmental Sciences & Ecology